2019
DOI: 10.31362/patd.517468
|View full text |Cite
|
Sign up to set email alerts
|

Yarı kırsal alanda 6-14 yaş grubu çocuklarda obezite sıklığı ve ilişkili faktörler

Abstract: Özet Amaç: Bu çalışmada Denizli İli Serinhisar İlçesi'nde bulunan ilkokul ve ortaokullarda öğrenim gören 6-14 yaş grubu çocuklardaki fazla tartılılık/obezite prevalansı ve ilişkili faktörlerin belirlenmesi amaçlanmıştır. Gereç ve Yöntem: Kesitsel tipteki bu araştırmanın evrenini Denizli İli Serinhisar İlçesi'ndeki devlet okullarında öğrenim gören tüm 6-14 yaş grubu öğrenciler oluşturmaktadır. Örneklem seçilmemiş olup evrenin tamamına ulaşılması hedeflenmiştir. Çalışmaya katılmayı kabul eden 1253 öğrenci (%82,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…It is though that mechanisms such as autonomic dysfunction, increased insülin level, vascular impairment in while it was <2.500 g in 10.6% of obese children and in 21.9% of non-obese children. The likelihood of obesity was 3.38 folds (1.67-6.86) higher in children with birth weight >4.000 g. In a study on 1.253 student aged 6-14 years, it was found that the obesity incidence was significantly higher among children with higher birth weight in agreement with our study (18). In a largescale study on children aged 9-11 years, it was found that the obesity risk was higher in children with birth weight>4.000 g when compared to those with low birth weight (19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is though that mechanisms such as autonomic dysfunction, increased insülin level, vascular impairment in while it was <2.500 g in 10.6% of obese children and in 21.9% of non-obese children. The likelihood of obesity was 3.38 folds (1.67-6.86) higher in children with birth weight >4.000 g. In a study on 1.253 student aged 6-14 years, it was found that the obesity incidence was significantly higher among children with higher birth weight in agreement with our study (18). In a largescale study on children aged 9-11 years, it was found that the obesity risk was higher in children with birth weight>4.000 g when compared to those with low birth weight (19).…”
Section: Discussionsupporting
confidence: 91%
“…On contrary to literature, it was found that there was no association between obesity and type of infant feeding in our study. In similar studies, no association of breastfeeding or duration of breastfeeding with obesity has been shown (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 82%